LEVEL OF KNOWLEDGE ABOUT MOM CHILDBIRTH PERINEAL STITCHES CARE IN THE JASMINE 1 RSUP Dr.SOERADJI TIRTONEGORO KLATEN - Lusmi Jumeita Damanik; Slamet Widodo; Evy Ernawati (STIKES DUTAGAMA KLATEN, 2012)
Background: Treatment includes cleaning the perineum in the female external genetalia. The procedure is usually carried out during the bath. Most women make their own perineal care areas when they are physically able. Perineal care can prevent and control the spread of infection, prevent skin damage, increase comfort and maintain the cleanliness (A.Griffin Perry and Patricia A. Potter, 2000). Based on preliminary studies by the author in February-April 2011 in Room Jasmine Dr Dr.Soeradji Tirtonegoro Klaten I have 359 deliveries, 290 or 80.7% of patients experiencing perineal sutures be caused due to rupture of the perineum during delivery and episiotomy scars.Methods: This type of study used is quantitative descriptive. Researchers used the study design was cross sectional. Sampling techniques in the study was purposive sampling by the number of respondents were 30 respondents. Data gathering knowledge about perineal wound care stitches using a questionnaire.Result: Based on table 4.1 above can be seen that the level of knowledge about the care she Ruling perineal stitches that qualify as either 23 people (76.67%), good enough 6 people (20.00%) and a less good one man ( 3.33%). It can be concluded that the postnatal maternal knowledge about perineal wound care either partially included in the criteriaConclusion: The level of knowledge about the care she Ruling stitches in the perineum jasmine 1 Dr Dr. Soeradji Tirtonegoro Klaten in either category.Suggestions: For mothers about childbirth perineal wound care stitches in one department of Dr Jasmine Room. Soeradji Tirtonegoro Klaten to actively seek information about wound care stitches through both the local midwife and guidance to the nearest health facility.